In vitro and in silico perspectives on the activation of antioxidant responsive element by citrus-derived flavonoids - Guan, Tianzhu; Bian, Canfeng; Ma, Zheng (Frontiers in Nutrition, 2023)
Oxidative stress plays an essential role in the pathogenesis of chronic diseases. Disrupting the Keap1-Nrf2 pathway by binding Keap1 is identified as a potential strategy to prevent oxidative stress-related chronic diseases. Therefore, of special interest is the utilization of dietary antioxidations from citrus, including narirutin, naringenin, hesperetin, hesperidin, naringin, neohesperidin dihydrochalcone, neohesperidin, and nobiletin, has been exploited as a prospective way to treat or prevent several human pathologies as Keap1-Nrf2 inhibitors for modulation of antioxidant properties.To probe into the structural foundation of the molecular identification of citrus-derived antioxidations, we calculated the antioxidant responsive element activation ability of citrus-derived flavonoids after binding with Keap1. Also, the quantum chemistry properties and binding mode were performed theoretically with frontier molecular orbitals, molecular electrostatic potential analysis, molecular docking, and absorption, distribution, metabolism, excretion (ADME) calculation.Results and discussion: Experimental findings combining computational assays revealed that the tested citrus-derived flavonoids can be grouped into strong agonists and weak agonists. The citrus-derived antioxidations were well housed in the bound zone of Keap1 via stable hydrogen bonding and hydrophobic interaction. Eventually, three of eight antioxidations were identified after ADME and physicochemical evaluations. The citrus-derived flavonoids were identified as potential dietary antioxidants of the Keap1-Nrf2 interaction, and can be used to improve oxidative 3 stress-related chronic diseases.